1999
DOI: 10.1034/j.1399-3011.1999.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide derivative synthesis catalyzed by Pseudomonas aeruginosa elastase

Abstract: Pseudomonas aeruginosa elastase was used to synthesize various N-protected dipeptide amides. The identity of the products was confirmed by FAB(+)-MS. After recrystallization, the yield of their synthesis was calculated, their purity was checked by RP-HPLC and their melting point was measured. With regard to the hydrolysis, it is well-established that the enzyme prefers hydrophobic amino acids in P'1 position and it has a wide specificity for the P1 position. This specificity was demonstrated to be quite unchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We speculate that the N-terminal Aib residue effectively protects this peptide from degradation by plasma proteases. As reported previously, Aib does not interact with the serine proteases elastase and thermolysin (Rival et al, 1999), and the introduction of Aib into a peptide backbone thus represents a useful strategy for enhancing its resistance toward proteases. Previous research has indicated that Aib tends to favor the formation of a helical conformation and this effect was reported to be more obvious when Aib is located in the inner region of the sequence (Conlon et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…We speculate that the N-terminal Aib residue effectively protects this peptide from degradation by plasma proteases. As reported previously, Aib does not interact with the serine proteases elastase and thermolysin (Rival et al, 1999), and the introduction of Aib into a peptide backbone thus represents a useful strategy for enhancing its resistance toward proteases. Previous research has indicated that Aib tends to favor the formation of a helical conformation and this effect was reported to be more obvious when Aib is located in the inner region of the sequence (Conlon et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…The peptide synthesis was carried out by a stepwise solidphase method utilizing 9-‰uorenylmethoxycarbonyl chemistry. 9,10) Tryptic digestion assay. N-Tosyl-L-phenylalanyl chloromethyl ketone-treated trypsin (Worthington, Lakewood, NJ, U.S.A.) was used for the digestion assay.…”
Section: Methodsmentioning
confidence: 99%
“…In their enzymatic peptide synthesis studies, Rival et al have reported that Aib did not interact with these two proteases. 10) Apparently, these two proteases did not recognize the Aib residue in the peptide sequence. In the present study, we used tryp- sin, also one of the serine proteases, as a speciˆc endopeptidase for the Lys residues present in BKBA-20.…”
mentioning
confidence: 99%
“…Furthermore, stability data in serum revealed that ∼40% of the original amount of peptide 2 remained after 16 h from the addition of bovine serum (Figure ), highlighting a prolonged half-life compared to most gene-encoded AMPs including the same parent peptide 1 , the amount of which decreased to 21% after 5 h incubation with fresh human serum . This is likely due to the presence of the noncoded Aib that should protect the peptides from degradation by plasma proteases, by preventing their interaction with the serine proteases elastase and thermolysin . In support of this, Hirano and co-workers designed analogs of the Stripe peptide (21 residues long), carrying different α,α-disubstituted amino acids or side-chain stapling to stabilize their helical structures.…”
Section: Discussionmentioning
confidence: 83%